(untitled) (Global Journals of Research in Engineering, 2023)
Smart cities are becoming a preoccupation for all life facilities Every single day smart cities become an urgent need to solve the problems of population increase and increase the amount and diversity of data over time Although the task is not easy to transform into smart cities the availability of some technologies makes the mission easier for us In this paper we reviewed the most prominent technologies used in smart cities and we made a general overview of the most trending technologies that are used in smart cities